2020
DOI: 10.3390/w12082154
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Vertical Distribution of Two Cladoceran Species in the Nakdong River Estuary, South Korea

Abstract: As cladocerans are a primary food source for fish, predator avoidance is important to sustain cladoceran populations. We hypothesized that Bosmina longirostris and Daphniaobtusa would show different vertical distributions that depend on environmental variables and their life cycle phase. Quarterly monitoring was implemented in three water column layers (upper, middle, and bottom) in the Nakdong River Estuary. Cladocerans were mostly observed during summer; B. longirostris and D.obtusa were most abundant and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Therefore, some cladoceran species avoid predators by distributing themselves in spaces where predators are reluctant to go (e.g., areas with low DO or phytoplankton) or face difficulties in search for food. The bottom layers of lakes and reservoirs [ 67 , 68 ] and spaces covered by aquatic macrophytes [ 69 , 70 , 71 ] have been suggested as representative refuge spaces for cladocerans to avoid predators. Fish that search for food using vision restrict themselves from foraging activities in spaces complexly created by the leaves and stems of aquatic macrophytes or deep-water levels with low light penetration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some cladoceran species avoid predators by distributing themselves in spaces where predators are reluctant to go (e.g., areas with low DO or phytoplankton) or face difficulties in search for food. The bottom layers of lakes and reservoirs [ 67 , 68 ] and spaces covered by aquatic macrophytes [ 69 , 70 , 71 ] have been suggested as representative refuge spaces for cladocerans to avoid predators. Fish that search for food using vision restrict themselves from foraging activities in spaces complexly created by the leaves and stems of aquatic macrophytes or deep-water levels with low light penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and Choi [ 68 ] suggested that high turbidity at the bottom layer of an estuary of the Nakdong River, which has a relatively low water depth, induced diel vertical migration of D. obtusa . Inorganic or organic materials transported from the upper and middle streams of the Nakdong River are accumulated in this area, and turbidity of the bottom layer is high owing to the high residence time of those materials.…”
Section: Discussionmentioning
confidence: 99%
“…Choi and Kim [ 44 ] pointed out that frequent movements of pelagic cladocerans, including D. obtusa , make them easy prey for predators searching for food. As long as there is no refuge, such as aquatic macrophytes in freshwater ecosystems, D. obtusa numbers can be very low or absent due to the continuous foraging activity of fish on cladocerans [ 19 , 45 ]. In particular, it is more difficult for D. obtusa to inhabit areas when fish specialize in the predation of cladocerans, such as Lepomis macrochirus in Korea’s freshwater ecosystems [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lack of light and the low dissolved oxygen in the hypolimnion of lakes and reservoirs restrict fish distribution; thus, the deeper layer can be used as shelter by some zooplankton species ( Daphnia spp. ; [ 22 , 23 , 24 ]). Empirical studies explain that the use of refuges by zooplankton is more of an evolutionary mechanism than one with morphological changes, such as increases in length of the head or spin [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%